Strategi Branding Teknologi Digital dalam Meningkatkan Jumlah Peserta Didik di Madrasah Tsanawiyah Pesantren Al Amin Mojokerto - Deden Daud Surahman; Rezki Nurma Fitria (Universitas Palan, 2023)
The research took place at Pondok Pesantren Al Amin Mojokerto institution (MTs) Pesantren Al Amin. In this research, the type used is qualitative by using a case study approach. Subjects conducted in the study were sourced from the Head of Public Relations, the Admissions Division and the Principal. In carrying out the research, the researcher collected some data from field observations, documentation studies, and analysis that the researcher used with triangulation.researchear has hopes and goals to be able to find out related to the implementation of digital technology branding strategies carried out at the Al Amin Islamic boarding school which is focused on the Madrasah Tsanawiyah (MTs) Pesanten Al Amin Mojokerto in order to have an interest in the branding carried out so that it can have a positive impact on joining the Al Amin madrasah educational institution. The results of the research that has been done are: The digital technology branding strategy carried out by the Al Amin Islamic Boarding School institution is by using line expansion, Brand Extensions, Co-Brand. Furthermore, in the process of branding strategies to support success in increasing the number of students and becoming Top Of Mind in the community, it is measured using brand attractiveness, brand loyalty. The implementation of the strategy has been successfully implemented in obtaining an increase in the quality of the Pondok Madrasah Al Amin institution to become famous in supporting its technology brand